(untitled) (Texas Journal of Engineering and Technology, 2023)
The article presents that reading fluency is the ability to read with sufficient ease and accuracy that one can focus attention on the meaning and message of the text. Reading fluency is most commonly assessed by listening to learners as they read aloud. When readers lack fluency, their oral reading sounds hesitant, lacking the accuracy, rhythm and flow that indicate confident understanding of the text